The Mediating Role of Organizational Support in the Effect of Perceived Democratic Leadership on Workplace Happiness (Third Sector Social Economic Review, 2025)
Democratic leadership strengthens the perception of organizational support by valuing employees' opinions and encouraging participation through its structure. As employees feel valued and supported, they become happier at work. Thus, a positive and complementary relationship exists between democratic leadership, organizational support, and workplace happiness. This study examines the mediating role of organizational support in the effect of democratic leadership on workplace happiness, analyzing its positive and negative aspects. The research was conducted with 396 employees at a textile company in Bursa; 298 questionnaires were suitable for analysis. Based on the factors obtained from the research, a research model was created. The correlation method was used to test the model's inter-scale relationships and the macro process model-4 analysis method was used to test the mediating role. The mediating role of organizational support in the effect of perceived democratic leadership on workplace happiness was significant and positive. Findings regarding the mediating role of organizational support reveal that it is an important variable in the relationship between democratic leadership and workplace happiness. In conclusion, this study offers a unique theoretical and practical perspective by incorporating the mediating role of organizational support into the existing literature on democratic leadership and workplace happiness.
Keywords: Leadership; Democratic Leadership; Workplace Happiness; Organizational Support